ASSESSMENT OF CIRCULARITY POTENTIAL IN FAÇADES OF HIGH-RISE BUILDINGS IN BELGRADE - Andjela Posavec; Budimir Sudimac; Miomir Vasov; Kevin Warmbold; Georg Klaus (Facta Universitatis. Series: Architecture and Civil Engineering)
A growing trend in the construction of high-rise buildings is currently prevalent in Belgrade, where more high-rise buildings have been built in the last decade than in the previous 50 years. However, these buildings have a significant negative impact on the environment, as their sophisticated construction technologies demand substantial resources and energy consumption. The aim of this research is to assess the possibility of reducing the resource consumption of these buildings, focusing on the circularity potential of their façades. The research is conducted on typical façades of high-rise buildings in Belgrade. The applied methodology for assessing the circular potential of façades relies on numerical calculations of material circularity indicators and CO2 emissions. Research findings draw conclusions about the circular potential at the beginning and end of the façade's lifecycle, covering the production, dismantling and disposal phases of integrated components. The study highlights differences in resource consumption based on the architectural characteristics of the examined façades and provides insights for their improvement through the implementation of materials with higher circularity potential and optimized impacts on the environment.